Critical assessment and thermodynamic modeling of the Al–C system. (September 2019) - Deffrennes, G.; Gardiola, B.; Allam, M.; Chaussende, D.; Pisch, A.; Andrieux, J.; Schmid-Fetzer, R.; Dezellus, O.
Abstract: The Al–C system is the backbone of wide variety of applications in multicomponent systems, and was therefore studied intensively. Yet, considerable disagreements remain in the reported data, and the phase equilibria in the binary system as well as the standard enthalpy of formation of Al4 C3 are still debated. In order to establish a reliable thermodynamic description of the Al–C system a thorough and critical assessment of the literature was conducted. The data on the solubility of carbon in liquid Al and on the thermodynamic properties of Al4 C3 were assessed, and the peritectic decomposition temperature of Al4 C3 was confirmed at 2425 ± 15 K by thermal analysis. Thermodynamic modeling of the Al–C system is provided and compared to previous works. The proposed description was found to be more robust and to carry more physical meaning than any previous modeling of the system, which imply an easier extrapolation of the binary into higher-order systems.